Transformasi Model Pembiayaan Saran Dan Prasarana Dalam Lembaga Pendidikan Islam Melalui Pendekatan Berbasis Keberlanjutan - Juhairiyah; Nurhadi, Ali; Umi Khoiroh, Anisya; Sofyan, Ahmad; Nur Aini , Intan (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to examine the transformation of the financing model for facilities and infrastructure in Islamic educational institutions through a sustainability-based approach. The formulation of the problem in this article includes: 1). What are the conditions and challenges in the financing model for facilities and infrastructure in Islamic educational institutions, 2). What strategies can be applied in transforming the financing model to be more sustainable, 3). To what extent is the effectiveness of the sustainability-based approach in improving the quality of independence of Islamic educational institutions. By using a literature study research method, by reviewing relevant literature such as books, journals, and education policy reports. The results of this study show that the financing conditions for facilities and infrastructure in Islamic educational institutions still face various challenges. Transformation of the financing model can be carried out through a strategy of diversifying sources of capital, strengthening financial governance, and multi-sector collaboration, and a sustainability-based approach has proven effective in improving the quality of educational infrastructure and strengthening the financial independence of institutions, provided that there is managerial commitment and supporting policies.